2013 6th International IEEE/EMBS Conference on Neural Engineering (NER) 2013
DOI: 10.1109/ner.2013.6696021
|View full text |Cite
|
Sign up to set email alerts
|

Silicon carbide neural implants: In vivo neural tissue reaction

Abstract: Novel materials are needed for intracortical neural implants (INI) to extend their reliability and functionality beyond a few years. Cubic silicon carbide (3C-SiC) is a chemically inert, physically robust semiconductor that has shown, through extensive in vitro testing, a high biocompatibility with neural cells. Recently we have shown that 3C-SiC does not attract a negative immune response from microglia in vivo, but the implants size did not allow adequate investigation of tissue response [1]. We produced a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…In a previous study [13], it was observed that cubic silicon carbide (3C-SiC) is highly compatible with CNS tissue in a murine mouse model. Therefore, in this work, we opted for 3C-SiC as the most adequate material to define a permanent implantable neuronal prosthesis.…”
Section: A Silicon Carbide (3c-sic) Neural Interfacementioning
confidence: 98%
See 1 more Smart Citation
“…In a previous study [13], it was observed that cubic silicon carbide (3C-SiC) is highly compatible with CNS tissue in a murine mouse model. Therefore, in this work, we opted for 3C-SiC as the most adequate material to define a permanent implantable neuronal prosthesis.…”
Section: A Silicon Carbide (3c-sic) Neural Interfacementioning
confidence: 98%
“…Our solution relies on two features: (1) we use a chip designed to operate with a power consumption that is small enough for it to be powered by radio frequency antennas, dispensing with the need for batteries; (2) we use a probe manufactured from silicon carbide (SiC), a material that demonstrated excellent neural compatibility with murine mouse brain tissue in vivo [13]. This paper presents the first version of the Cortex chip, which is a 4-channel amplifier that magnifies neural signals to levels high enough for them to be processed by a computer.…”
Section: Introductionmentioning
confidence: 99%
“…At this stage it is useful to review some of the important biomedical devices that have been reported and use SiC materials. Indeed, SiC has been used in virtually every part of the human body, from a durable coating for bone prosthetics [38] and in dental applications [39], which cover the mechanical/structural biomedical use of SiC, to coatings for brain-machine-interface (BMI) devices [7,28,[40][41][42][43][44], myocardial heart probes [45,46] and finally non-fouling coatings for coronary heart stents [10,30,47]. A plethora of sensors have been reported and, at this point, it is sufficient to review the literature for a sampling of this important work [26].…”
Section: Silicon Carbide and The Biological Interfacementioning
confidence: 99%
“…d An incubation device with PID controlled temperature and CO 2 saturation which will allow the MEA to be used for long term neuroscience experiments material uses most of the processing techniques available from the Si semiconductor device industry. Here we report some of the initial in vivo reactions from CNS microglia to an neural implant composed of 3C-SiC(100) [41,155].…”
Section: Neural Probes and Mea'smentioning
confidence: 99%
See 1 more Smart Citation